The Effect of Schools Principal Supervision and Moderated Work Motivation Online Learning Methods on the Performance of Teachers of SMAN 25 Tangerang Regency - Cepih Cepih; Peni sawitri (Dinasti Publisher, 2022)
This study aims to analyze (1) Principal's supervision of teacher performance at Sman 25 Tangerang Regency (2) teacher performance motivation on teacher performance results at Sman 25 Tangerang Regency (3) Online learning on teacher performance results at SMAN 25 Tangerang Regency. This study uses quantitative methods and uses a questionnaire as a research instrument. The data were collected from 56 respondents from teachers at 25 district of Tangerang. The collected data were then analyzed using simple linear regression analysis methods and multiple linear regression analysis using a quantitative approach. The results of the analysis show that (1) the principal's supervision variable (X1) has a partial significant effect on teacher performance. This is indicated by the value of the regression coefficient (X1) of 0.000 <0.05 (2) The variable of teacher work motivation (X2) has a significant effect on teacher performance. This is shown by the regression coefficient value of X2 of 0.036 <0.05 and ( 3) The online learning variable (X3) has a significant effect on performance, as can be seen from the regression coefficient (X3) of 0.000 <0.05, which has a positive effect on teacher performance results. The principal's supervision variable, work motivation, online learning is obtained a calculated F value of 57.819 with a significant number (P value) of 0.000 meaning that the principal's supervision variable, work motivation, online learning has a significant influence simultaneously on the teacher performance variable.